Implementation Of Street Children Handling Strategies By The Social Services Department Of Mataram City - Putri Nurbaiti Utama; Eddy Supriyadinata Gorda (Eduvest - Journal of Universal Studies, 2024)
This study analyzes the implementation of the street child handling strategy by the Mataram City Social Service. The problem of street children in Indonesia, especially in Mataram, is a complex social issue, with many contributing factors, including poverty and unemployment. Although there is a legal basis that supports child protection and empowerment, practice in the field shows significant obstacles in policy implementation. This study uses a qualitative descriptive approach and involves interviews and observations. The results of the study revealed that the efforts of the Social Service are still hampered by limited human and financial resources, as well as a lack of coordination. This research is expected to provide recommendations for improving public policies related to the handling of street children in Mataram City.